Rasch model analysis of learning interest instrument for mathematics education students in statistical course - Ahmad Lutfi; Husnul Khatimah Rusyid; Ahmad Mukhibin; Hevy Risqi Maharani (Journal on Mathematics Education Research (J-MER), 2023)
This study aims to comprehensively examine the quality of mathematics learning interest instruments in terms of validity, reliability, undimensionality, distribution of abilities, and suitability of student responses. So, this research uses a survey-based quantitative descriptive method. Data collection was done by distributing a learning interest questionnaire consisting of 25 statements to mathematics education students who were in the 4th semester at one of the universities in Semarang. The results showed that the learning interest instrument used was valid and reliable so that the instrument could be used to measure student learning interest. The distribution of the items also shows that most students admit to having a high interest in learning statistics courses. Analysis of the suitability of student responses shows that 21 statements describe the suitability between learning interests and responses given by students. Meanwhile, 4 other statements showed discrepancies.